P125 Review: use of digital sexual health services by under-16s and an evaluation of safeguarding procedures. (8th June 2017) - Bakhai, Minal; Perera, Sean
Abstract : Introduction: Digital health is an increasingly popular way to access health services, particularly by young people. There is a paucity of research exploring the use of e-health services by under–16s. As an online doctor service offering sexual health services to adults, we conducted a review of under-16s trying to access services and an evaluation of safeguarding procedures. Methods: A retrospective audit of under-16s trying to access e-sexual health services between January–December 2015. Results: 66 patients were identified (a 4-fold increase since 2008). 71.2% were female and mostly distributed in urban areas. The most frequently accessed services were emergency contraception (27.3%) and regular contraception (43.9%). 22.7% (n15) entered an incorrect date of birth. 77.3% (n51) completed a safeguarding assessment with a doctor via telephone, guided by 'Spotting the Signs', in addition to answering a questionnaire online. Safeguarding concerns were identified in 39.2% (n20) of these children and referred to social services. The remainder underwent GP follow-up. All were directed to appropriate face-to-face services. Discussion: Our data shows increasing access by under-16s to e-sexual health services. A significant proportion were identified as being at-risk of sexual exploitation. A telephone safeguarding assessment in addition to our online evaluation was an effective method for identifying safeguarding concerns. Alongside IT systems to prevent those trying to bypass checks online, many of our services (including contraception and emergency contraception) require attendance to pharmacy. The use of our pharmacy network in undertaking identity checks and face-to-face safeguarding screening is invaluable in supporting the ongoing safety of children.